Enhancing Students’ Tourism English Competence through a Triadic Model of Humanities, Applied Linguistics, and Tourism Studies - Laba, I Nengah; Narlianti, Ni Putu Veny (International Journal of Linguistics and Discourse Analytics, 2025)
Tourism English competence is increasingly essential in global tourism environments, where effective communication requires more than linguistic accuracy—it demands intercultural awareness, cultural interpretation, and context-sensitive interaction. Conventional language instruction that focuses primarily on grammar and vocabulary has proven inadequate for preparing learners to meet the pragmatic, sociocultural, and professional communication needs of the tourism industry. This study proposes a triadic model, an interdisciplinary pedagogical framework that integrates humanities, applied linguistics, and tourism studies to enhance students’ Tourism English competence in a comprehensive and culturally informed manner. The model was implemented with forty-seven vocational students and tourism practitioners in Bali and assessed through pre- and post-test measures across four domains of communicative competence. The results revealed substantial improvements across linguistic, sociolinguistic, discourse, and strategic competencies, underscoring the effectiveness of culturally grounded, communicatively oriented, and practice-integrated instruction. These findings indicate that the triadic model provides a robust and transformative framework for Tourism English education, particularly in culturally rich destinations where professional communication hinges on the integration of language proficiency, cultural literacy, and service excellence.